2010
DOI: 10.1016/j.brainres.2009.11.084
|View full text |Cite
|
Sign up to set email alerts
|

Impaired spine formation and learning in GPCR kinase 2 interacting protein-1 (GIT1) knockout mice

Abstract: The G-protein coupled receptor (GPCR)-kinase interacting proteins 1 and 2 (GIT1 and GIT2) are scaffold proteins with ADP-ribosylating factor GTPase activity. GIT1 and GIT2 control numerous cellular functions and are highly expressed in neurons, endothelial cells and vascular smooth muscle cells (VSMC). GIT1 promotes dendritic spine formation, growth and motility in cultured neurons, but its role in brain in vivo is unknown. By using global GIT1 knockout mice (GIT1 KO), we show that deletion of GIT1 results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
43
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 49 publications
8
43
1
Order By: Relevance
“…2b). GIT1 deficiency markedly affected survival; ~50% of Git1 −/− mice died postnatally, as reported previously 18,22 . Git1 −/− mice that survived weighed 60-70% that of wild-type (WT) mice and had a normal appearance.…”
Section: Git1 Is Associated With Adhd In Humans and Adhd-like Behaviosupporting
confidence: 54%
See 1 more Smart Citation
“…2b). GIT1 deficiency markedly affected survival; ~50% of Git1 −/− mice died postnatally, as reported previously 18,22 . Git1 −/− mice that survived weighed 60-70% that of wild-type (WT) mice and had a normal appearance.…”
Section: Git1 Is Associated With Adhd In Humans and Adhd-like Behaviosupporting
confidence: 54%
“…In rodent brains, GIT1 regulates neurite outgrowth 13,14 , spine morphogenesis 15,16 , synapse formation 15-20 and synaptic receptor localization of the glutamate receptor AMPA 21 . Git1-null (Git1 −/− ) mice show impaired dendritic outgrowth, reduced spine density, impaired fear responses and reduced adaptation to new and changing environments 18,22 . GIT1 associates with huntingtin, a protein implicated in Huntington's disease 23 .…”
mentioning
confidence: 99%
“…Importantly, although Git1-knockout mice were susceptible to early postnatal death, survivors developed normally and did not show any gross anatomical abnormalities (Schmalzigaug et al 2009). In another study, the neurons of Git1-knockout mice exhibited decreased dendritic lengths and spine densities in the hippocampus (Menon et al 2009). Moreover, behavioural analysis showed that these mice adapt poorly to new or changing environments (Menon et al 2009).…”
mentioning
confidence: 96%
“…In another study, the neurons of Git1-knockout mice exhibited decreased dendritic lengths and spine densities in the hippocampus (Menon et al 2009). Moreover, behavioural analysis showed that these mice adapt poorly to new or changing environments (Menon et al 2009). Won et al (2011) investigated 27 single nucleotide polymorphisms (SNPs) in the GIT1 gene; only the rs550818 polymorphism, located in intron 20, was associated with ADHD susceptibility in a sample of Korean children.…”
mentioning
confidence: 96%
“…Interestingly, β-PIX also binds to PAK (p21 activated kinase) via an N-terminal SH3 domain (Mott et al 2005), suggesting that the GIT1/β-PIX/PAK complex can organize and regulate β-PIX GEF activity and the Rac-mediated activation of PAK. Loss of GIT1 in mice results in reduced dendritic arborization and spine density and in multiple Attention Deficit Hyperactivity Disorder (ADHD)-like behaviors (Won et al 2011;Menon et al 2010;Schmalzigaug et al 2009). Importantly, GIT1 SNPs (single nucleotide polymorphisms) that reduce GIT1 expression are associated with human ADHD (Won et al 2011).…”
Section: A Git1 and Rac Signaling Scaffold Involved In Synaptogenesismentioning
confidence: 99%